'To give an outsider an idea of what it could be like': A case study of the creative representation of hearing voices. (February 2018) - Flavin, Michael; James, Bethany
This paper reports on a case study which aims to recreate the hearing voices symptom in schizophrenia. The case study was submitted for a co-curricular module at King's College London by a first-year undergraduate Music student, Bethany James, and was created using the web application, Mahara. The core of the case study consists of a soundscape of both everyday and unusual sounds, in conjunction with an original musical composition. The paper describes the case study and discusses it using chaos narrative as an analytical lens. The paper argues that the case study ('A Beautiful Mind – Artefact') effectively evokes the hearing voices symptom, conveying a lucid sense of the experience to non-sufferers and thus potentially creating use value for clinicians and care workers.